COVID-19 in China: From epidemiology to treatment (Review) - Chen, Hongtao (Exp Ther Med, 2020)
Coronavirus disease 2019 (COVID-19) is a newly emerging infectious disease caused by the novel coronavirus SARS-CoV-2. It first became prevalent in Wuhan, Hubei, China in December 2019. COVID-19 was initially characterized by pneumonia of unknown etiology, accompanied by fever, dry cough and fatigue. Due to its highly infectious nature it rapidly led to widespread human infection, causing 80,924 confirmed cases and 3,140 mortalities in mainland China as of March 9, 2020. The present review highlights the prevalence of COVID-19 in China, the etiology, pathology, clinical presentation, laboratory and chest imaging tests, and treatment of this disease.